Analisis Perencanaan Supply Chain Management pada Seneca Coffe Studio Kota Medan - Vania Sally Nabila; Minta Ito Lubis; Siti Aisyah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The development of food and beverage sales is growing rapidly. One of the drinks that has experienced a large increase in sales is coffee. With the potential for the development of coffee sales, to have an advantage in the sales competition, Seneca Coffee Studio needs to implement Supply Chain Management. The purpose of using Supply Chain Management, where the most basic is to be able to align demand with existing supply. This research method is a qualitative method that focuses on analyzing the application of Supply Chain Management at Seneca Coffee Studio. The results of this study are the supplier selection process at Seneca Coffee Studio with the initial process of taking coffee beans from the Samosir coffee plantation to logistics distribution. The supply of coffee from Samosir coffee plantations to Seneca Coffee Studio greatly helps the distribution of coffee supplies to Seneca Coffee Studio outlets and has an impact on the sale of coffee drinks. The purpose of this study was to determine the process of supplier selection, logistics planning, and logistics distribution at Seneca Coffee Studio. This study uses qualitative methods with data collection techniques by observation and interviews.